OPTIMIZING ELDER CARE DURING CRISIS: LESSONS LEARNED FROM VENEZUELA. (11th November 2018) - Tucker, J; Dávila, C
Abstract: Disasters, whether natural or human-induced, disproportionately impact older adults. Venezuela is currently facing the worst economic crisis in its history with the highest inflation rate in the world, the highest homicide rate in the world, and severe shortages of food, water, and medicine. This presentation discusses a two-year longitudinal study we conducted on older adult caregiving in Caracas, aiming to describe how some health care providers and communities adapted to meet elder care needs during the crisis. Combining anthropological and gerontological social work approaches, qualitative research was conducted in community health clinics and older adult community groups. This study's research design uses ethnographic interviews (n=55) and direct observation of both older adults and health care providers. Examples of findings include 1) providers' reliance on medical technology shifted to reliance on the clinical expertise of senior physicians and 2) older adults adapted with a form of self-triage through prioritizing and rationing the treatment of their medical conditions. This presentation will conclude with practice recommendations based on inspiring cases of optimized care practices during the crisis.